STRATEGI PENGEMBANGAN AGRIBISNIS BUAH NAGA ORGANIK DI KABUPATEN WONOGIRI - Paundrianagari, Sabila Ajeng; Setyowati, Nuning; Qonita, RR. Aulia (Agribusiness Department, Agriculture Faculty, Tanjungpura University, 2019)
The research aimed to identify internal factors that become strengths and weaknesses as well as external factors that become opportunities and threats, formulate alternative development strategies, and formulate priority strategies that can be applied in the development of organic dragon fruit agribusiness in Wonogiri Regency. The basic method used is descriptive and analytical. Determination of the location of the study was carried out purposively, namely the Beji Makmur Farmers Group Association in Beji Village, Nguntoronadi District, Wonogiri Regency, the method of determining the Key Informants was chosen purposively. The types of data used are primary data and secondary data. The analytical method used is internal and external factor analysis, IFE and EFE matrix, IE matrix, SWOT matrix, and Analytical Hierarchy Process. The results of the research concluded that (1) The main factors of internal strength, namely marketing of organic dragon fruit have reached exports to Germany while the main weakness is the absence of the Beji Makmur Farmers Group Association secretariat, the main opportunity external factors namely the demand for organic dragon fruit in the form of fresh fruit while the main threat is erratic weather changes, (2) The alternative strategies for developing organic dragon fruit in Wonogiri Regency are SO, WO, ST, and WT strategy. (3) The development strategy priorities that can be applied in developing the Beji Makmur Farmers Group Association is to innovate by using radiation technology in the cultivation of organic dragon fruit so that productivity is more optimal.Keywords: Analytical Hierarchy Process (AHP), Development Strategy, Dragon Fruit, Organic, SWOT